2005
DOI: 10.1111/j.1875-595x.2005.tb00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of traumatised primary teeth in the west-Mediterranean region of Turkey

Abstract: The results of this study suggest that a preventive educational programme should be instituted, directed at parents and teachers at nursery schools, in order to inform them about what to do in dental trauma cases and the importance of immediate attendance for dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
4
11
2
Order By: Relevance
“…A lack of motor coordination 25,26 on walking and running is the main reason for TDI in preschool children, whereas in early school-age children, TDIs are most likely due to increased independence at school, playgrounds and sports 4,27,28 . In agreement with previous studies [18][19][20]29,30 , this study showed that TDI commonly involved maxillary incisors. Th is fi nding may be explained by the fact that these teeth may have inadequate lip coverage and frequently protrude 30 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…A lack of motor coordination 25,26 on walking and running is the main reason for TDI in preschool children, whereas in early school-age children, TDIs are most likely due to increased independence at school, playgrounds and sports 4,27,28 . In agreement with previous studies [18][19][20]29,30 , this study showed that TDI commonly involved maxillary incisors. Th is fi nding may be explained by the fact that these teeth may have inadequate lip coverage and frequently protrude 30 .…”
Section: Discussionsupporting
confidence: 81%
“…Th is fi nding can be explained by the periodontal ligament elasticity and alveolar bone resilience 26,30 . In permanent teeth, enamel-dentin fractures without pulp exposure were the most frequent type of injury, which is similar to other studies 12,15,[18][19][20]33 , but contrary to a group of studies that found enamel fracture to be the most frequent type of hard dental tissue injury [34][35][36][37] . In this study, there was a statistically signifi cant relationship between age, gender, location, and cause of injury (p<0.05).…”
Section: Discussioncontrasting
confidence: 34%
See 2 more Smart Citations
“…Swelling (5, 7) and coronary chipping (6, 8–11) were reported to be the most frequent traumas affecting the deciduous dentition. Several studies reported the highest prevalence of dental trauma in 3‐ to 5‐year‐old children (8–10, 12).…”
Section: Prevalence Of Dental Traumatic Injuries In Deciduous Teeth mentioning
confidence: 99%